The forecasting and analysis of oil spill drift trajectory during the Sanchi collision accident, East China Sea. (1st September 2019) - Li, Yan; Yu, Han; Wang, Zhao-yi; Li, Yun; Pan, Qing-qing; Meng, Su-jing; Yang, Yi-qiu; Lu, Wei; Guo, Kai-xuan
Abstract: On 06 January 2018, the Sanchi tanker collided with a Hong Kong-flagged cargo ship at 30°42′42″N, 124°56′42″E in the East China Sea (ECS). In this paper, we used a Northwest Pacific (NWP) operational oil spill forecasting system of National Marine Environmental Forecasting Center of China (NMEFC) to forecast the oil drifting trajectory during Sanchi collision accident. In order to reveal the major errors sources and improve the accuracy of the forecasting system, we designed five numeric simulation scenarios. In the five scenarios, we input the different current and wind forcing data into the forecasting system, and set the different oil released time. By the analysis and discussion of the five numeric simulation results, we drew the conclusions following: 1) The error of wind and the inaccuracy released time of oil were the major error sources of the NWP operational oil spill forecasting system of NMEFC during the accident. 2) We should further strengthen the observation of the complicated vortex region of Kuroshio Current to improve the prediction accuracy of material transport in ocean. 3) In the event that this information is unavailable, uncertainty analysis should be conducted by simulating the oil spill on all kinds of different released conditions. Highlights: We designed five numeric simulation scenarios to reveal the major errors sources. Wind error and inaccuracy released time of oil were the major error sources. We should further strengthen the observation of Kuroshio Current. Uncertainty analysis should be conducted if released time of oil is inaccuracy.